S6 Establishing the true incidence of hospitalised community acquired pneumonia (cap) in the uk: a hospital episode statistics (hes) analysis. (15th November 2017) - Campling, J; Jones, D; Ellsbury, G; Czudek, C; Madhava, H; Slack, M
Abstract : Introduction: In November 2015, the Joint Committee on Vaccination and Immunisation (JCVI) recommended against including PCV13 for age based and risk based populations. 1 A principal driver of this recommendation was the incidence of hospitalised pneumococcal pneumonia, reported by Rodrigo et al. 2 Using the Results from the study by Rodrigo et al a simple calculation can be performed to approximate the incidence of vaccine preventable pneumococcal CAP from all cause hospitalised CAP (ACH-CAP). The national Hospital Episodes Statistics (HES) database 3 reports a significantly higher incidence of ACH-CAP which could impact the potential benefit provided by PCV13. Aim: To compare the incidence of ACH-CAP reported in the study by Rodrigo et al. 2 with the incidence of ACH-CAP coded in HES in the corresponding population, over a similar period of time. Materials and Methods: The study by Rodrigo et al ran from September 2008 for 5 years. Inpatients≥16 years old, with symptoms suggestive of lower respiratory tract, new CXR infiltrates consistent with pneumonia, and treated for CAP, were included. 2 Our HES analysis included patients≥18 years old with (ICD-10) codes J12–J18 4 (April 2008 – March 2013) admitted to the hospitals in Rodrigo's study (Nottingham University Hospitals NHS Trust – City Campus and Queen's Medical Centre Campus). Results: Rodrigo and colleagues identified 2702 adults while our analysis of HES identified 11 059 across both sites. Conclusion: The study by Rodrigo et al was not specifically designed to capture total incidence of ACH-CAP, instead its objective was to report on pneumococcal serotype evolution. 2 Miscoding and misdiagnosis of pneumonia in HES is well-recognised 5 but doesn't appear to explain the four-fold difference in these numbers. Further investigation to validate HES data against hospital records could be performed. Accurate incidence data would impact cost-effectiveness analyses and facilitate a more informed decision next time the data is reviewed. Please refer to page A257 for declarations of interest in relation to abstract S6. References: https://app.box.com/s/iddfb4ppwkmtjusir2tc/1/2199012147/22846051967/1 Rodrigo et al . Eur Respir J 2015;45:1632–1641. http://content.digital.nhs.uk/hes http://www.icd10data.com/ICD10CM/Codes Daniel et al . Thorax 2017;72(4):376–379.